Fallen, Unrepentant, and Unforgiven: Calisto at «la Madalena» - David Burton (Celestinesca, 2021)
Fernando de Rojas makes few references to organized religion and to religious place names in La Celestina (1499). Concerning religious place names, the one specific reference is to the church of la Madalena where Calisto goes to pray. The act of praying at la Madalena is then repeated three times during the drama. Thus, Rojas presents the reader with yet another example of the irony that pervades his entire work. This essay examines the story and the legends associated with St. Mary Magdalene, demonstrating how Rojas’ purposeful references to this saint ironically comment upon Calisto’s intent to make Melibea his mistress.